HUBUNGAN TINGKAT PENGETAHUAN TENTANG KESEHATAN REPRODUKSI DENGAN PERILAKU MENJAGA KESEHATAN ORGAN REPRODUKSI PADA SISWI KELAS XI IPA SMA NEGERI JUMAPOLO KARANGANYAR - Ratna Indriati; Dwi Rindu Rusyati (KOSALA : Jurnal Ilmu Kesehatan, 2015)
Background. Reproductive health needs to be understood by teens because adolescence is a period where there is a rapid growth including reproductive function. The impact of not maintaining reproductive health that can arise various diseases of the reproductive organs. From the survey results the researchers did on 10 students of class XI IPA SMAN Jumapolo Karanganyar, obtained a yield of 7 students do not understand clearly about reproductive health and are still puzzled how care productive health.Research purposes. To determine the relationship of the level of knowledge about reproductive  health  to  maintain  a healthy  reproductive behavior of female students in high school students science class XI at SMAN Jumapolo Karanganyar.Methods. The research design correlation with the approach of cross sectional method. Subjects were 40 grader XI IPA SMAN Jumapolo Karanganyar with saturated sampling technique in which the entire population is used as a sample. Data obtained by questionnaire to determine the level of student knowledge about reproductive health and behavior of students in maintaining the health of the reproductive organs. The data obtained and analyzed by chi square test with P = 0.05. Results showed the level of student knowledge about reproductive health with high category as many as 29 people (72.5%) and medium category  11 people (27.5%) whereas students with behavioral maintain reproductive health as many as 25 children (62.5%) and students who do not take action maintain reproductive health as many as 15 people (37.5%).Results of analysis using the chi-square test was obtained p equal to 0.035 so that the value of p <0.05, which means that Ho is rejected and Ha accepted. The conclusion from this research is there is correlation between knowledge about reproductive health students with behavioral maintain reproductive health of female students in high school students science class XI  at SMAN Jumapolo Karanganyar.Keywords: Level of Knowledge, Reproductive Health, Behavioral Health